Effect of gait training using Welwalk on gait pattern in individuals with hemiparetic stroke: a cross-sectional study - Ii, Takuma; Hirano, Satoshi; Imoto, Daisuke; Otaka, Yohei (Frontiers in Neurorobotics, 2023)
Introduction: We aimed to explore the effect of gait training using Welwalk on gait patterns by comparing differences in gait patterns between robotic-assisted gait training using Welwalk and gait training using an orthosis in individuals with hemiparetic stroke. Methods: This study included 23 individuals with hemiparetic stroke who underwent gait training with Welwalk combined with overground gait training using an orthosis. Three-dimensional motion analysis on a treadmill was performed under two conditions for each participant: during gait training with Welwalk and with the ankle-foot orthosis. The spatiotemporal parameters and gait patterns were compared between the two conditions. Results: The affected step length was significantly longer, the step width was significantly wider, and the affected single support phase ratio was significantly higher in the Welwalk condition than in the orthosis condition. The index values of abnormal gait patterns were significantly lower while using Welwalk than in the orthosis condition. The following four indices were lower: contralateral vaulting, insufficient knee flexion, excessive hip external rotation during the paretic swing phase, and paretic forefoot contact. Discussion: Gait training using Welwalk increased the affected step length, step width, and single support phase, while suppressing abnormal gait patterns as compared to gait training using the ankle-foot orthosis. This study suggests that gait training using Welwalk may reacquire a more efficient gait pattern that suppresses abnormal gait patterns. Trial registration: Prospectively registered in the Japan Registry of Clinical Trials (https://jrct.niph.go.jp; jRCTs042180152).